2021
DOI: 10.1016/j.molmet.2021.101293
|View full text |Cite
|
Sign up to set email alerts
|

Specific amino acid supplementation rescues the heart from lipid overload-induced insulin resistance and contractile dysfunction by targeting the endosomal mTOR–v-ATPase axis

Abstract: Objective The diabetic heart is characterized by extensive lipid accumulation which often leads to cardiac contractile dysfunction. The underlying mechanism involves a pivotal role for vacuolar-type H + -ATPase (v-ATPase, functioning as endosomal/lysosomal proton pump). Specifically, lipid oversupply to the heart causes disassembly of v-ATPase and endosomal deacidification. Endosomes are storage compartments for lipid transporter CD36. However, upon endosomal deacidifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 43 publications
9
46
0
Order By: Relevance
“…It has also been shown that supplementing or promoting non-lipid myocardial metabolic substrates can improve the state of high-fat induced cardiac energy metabolism imbalance. In vitro and in vivo studies have demonstrated that specific amino acid supplementation (lysine, leucine, arginine) reinternalized CD36 to the endosomes by regulating the mTORC1-v-ATPase axis, reduces myocardial lipid uptake and reverses/prevents lipid accumulation 39 .…”
Section: Lipid Overload Resulted In Increased Fat/cd36 Translocation To the Cell Membrane And Decreased Glut4mentioning
confidence: 99%
“…It has also been shown that supplementing or promoting non-lipid myocardial metabolic substrates can improve the state of high-fat induced cardiac energy metabolism imbalance. In vitro and in vivo studies have demonstrated that specific amino acid supplementation (lysine, leucine, arginine) reinternalized CD36 to the endosomes by regulating the mTORC1-v-ATPase axis, reduces myocardial lipid uptake and reverses/prevents lipid accumulation 39 .…”
Section: Lipid Overload Resulted In Increased Fat/cd36 Translocation To the Cell Membrane And Decreased Glut4mentioning
confidence: 99%
“…Georgila et al showed that amino acid deprivation inhibited mTORC1 activity and thereby reduced ApoA-I protein levels, but not ApoA-I mRNA expression in HepG2 cells [ 18 ]. Moreover, a recent study by Wang et al showed that a cocktail of leucine, arginine, and lysine increased mTORC1 activation in HL-1 cells [ 29 ]. Therefore, we also evaluated the effects of individual amino acids on mTORC1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, specific mTORC1 activation by using the activator MHY1485 did not further increase ApoA-I mRNA expression or pro-ApoA-I levels. It is important to note that the previously mentioned studies used amino acid deprived cells that were only treated for 1–6 h [ 18 , 29 ]. Our cells were, however, treated for 48 h and were probably not enough deprived of amino acids to reduce the activity of the mTORC1 pathway due to the amino acids already present in the culture medium ( Supplementary Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was observed that specific amino acids also stimulate v-ATPase (re-)assembly to retain CD36 in the endosomes and reduce myocardial fatty acid uptake [ 29 ▪ ]. These novel findings combined indicate the application of specific amino acid supplementation for tuning of the contributions of fatty acids and of glucose to their current cellular demand so as to avoid both fatty acid overload (lipotoxicity) and glucose overload (glucotoxicity).…”
Section: Molecular Mechanism Of Subcellular Recycling Of Cd36mentioning
confidence: 99%
“…The recent disclosure of v-ATPase as regulator of CD36 recycling makes this endosomal enzyme an interesting candidate for modulation of sarcolemmal CD36 content. Indeed, as outlined above, specific amino acids increase myocardial v-ATPase activity thereby reducing sarcolemmal CD36, and ultimately preventing or restoring lipid overexposure-induced contractile dysfunction [ 29 ▪ ]. However, whether these amino acids act specifically on the heart or would also affect v-ATPase in other tissues has not yet been addressed.…”
Section: Cd36 As Target For Metabolic Interventionmentioning
confidence: 99%